2012
DOI: 10.3109/15563650.2012.655281
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits due to pesticide poisoning in South Korea, 2006–2009

Abstract: This study provide estimates for emergency department visits due to pesticide poisoning at the national level and suggests that pesticide poisonings, both intentional and unintentional, require significant public health interventions in South Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Acute poisoning by using pesticides remains to be a major cause for emergency visits to the hospitals in developing countries [8, 13, 16, 18, 25, 26]. This prospective hospital-based study explored the situation of pesticides poisoning in an agriculture intensive-district of Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Acute poisoning by using pesticides remains to be a major cause for emergency visits to the hospitals in developing countries [8, 13, 16, 18, 25, 26]. This prospective hospital-based study explored the situation of pesticides poisoning in an agriculture intensive-district of Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…The health authority maintains an accuracy assessment system and annually reports the results to the Ministry of Health and Welfare. In 2010, the NEDIS records were 98.8% complete with 89.3% reliability ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the Korea, previous epidemiologic studies have reported a 5.4 per 100,000 persons age-standardized pesticide poisoning death rate during 2006–2010, 4 an annual pesticide-related hospitalization rate of 17.8 per 100,000 persons during 2004–2006, 5 a 26.8 per 100,000 persons annual average rate of emergency department visits due to pesticide poisoning during 2006–2009, 6 and 24.7% of acute occupational pesticide poisoning among male farmers in 2010. 7 Recently, a remarkable decrease in suicide deaths from herbicide poisoning following the legislative ban of paraquat has been reported.…”
Section: Introductionmentioning
confidence: 99%